Corporate Social Responsibility's Influence on Product Innovation: Spotlight on the Mediating Role of Employer Branding (A Case Study of Medium and Large Manufacturing Firms in Bushehr City) - zahra hajizadeh; Ebrahim Rajabpour; Heidar Ahmadi; Majid Esmaeilpour (‫مدیریت بازرگانی)
Objective Corporate Social Responsibility (CSR) has become increasingly significant for managerial authorities striving for organizational success. Comprehensive CSR initiatives are essential to address the growing pressures for heightened CSR commitment in corporate entities. These innovations enhance organizational performance within communities and have positive implications for individuals, communities, and state sectors. This study aims to highlight the impact of CSR on product innovation, exploring the mediating role of employer branding within medium and large manufacturing companies of Southern Iran's Bushehr City.